Diazepam, in a single dose, inhibits cellular chemotaxis, macrophage stimulation, and TNF-α activity in LPS-induced acute inflammatory responses in mice (Revista Brasileira de Ciências Farmacêuticas, 2008)
Benzodiazepines are one of the most frequently prescribed drugs due to their anxiolytic properties. The aim of this study was to evaluate the effects of diazepam on lipopolysaccharide-induced peritoneal acute inflammatory responses. Swiss mice were treated with diazepam in a single dose of 1 or 10 mg/kg- subcutaneously 1 h before an intraperitoneal injection of lipopolysaccharide or sterile saline solution. The mice were killed 16 h after and the cells were washed from the peritoneal cavity to determine the total number of cells and the mononuclear and polimorfonuclear subpopulations, as well as the TNF-alpha activity and percentage of spread macrophages. Our results showed that the diazepam treatment (1 and 10 mg/kg) induced a significant reduction in the LPS-induced macrophage stimulation and TNF-α activity. Diazepam (10 mg/kg) also reduced the inflammatory cellular migration when compared to the control. It can be concluded that the diazepam treatment in a single dose is able to influence the inflammatory cellular influx, macrophage stimulation and TNF-α activity in the acute inflammatory response in mice, having possible implications on the anti-infectious response efficiency.